2023
DOI: 10.1371/journal.pone.0281530
|View full text |Cite
|
Sign up to set email alerts
|

Identification and functional analysis of protein secreted by Alternaria solani

Abstract: Early blight, caused by the necrotrophic fungus Alternaria solani, is an important foliar disease that causes major yield losses of potato. Effector proteins secreted by pathogens to host cells can inhibit host immune response to pathogens. Currently, the function of effector proteins secreted by A. solani during infection is poorly understood. In this study, we identified and characterized a novel candidate effector protein, AsCEP50. AsCEP50 is a secreted protein that is highly expressed throughout the infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Besides peptide effectors, Alternaria species can synthesise phytotoxic metabolites, such as AAL toxins and other host‐specific or host‐nonspecific toxins. Such toxins serve as chemical inhibition of defence compounds produced by the host or the induction of cell death (Wang et al, 2023). There is limited information on the specific role of toxins of A. solani in pathogen infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides peptide effectors, Alternaria species can synthesise phytotoxic metabolites, such as AAL toxins and other host‐specific or host‐nonspecific toxins. Such toxins serve as chemical inhibition of defence compounds produced by the host or the induction of cell death (Wang et al, 2023). There is limited information on the specific role of toxins of A. solani in pathogen infection.…”
Section: Discussionmentioning
confidence: 99%
“…There is limited information on the specific role of toxins of A. solani in pathogen infection. However, a recent study showed the effect of alternaric acid, a toxin of A. solani , on the hypersensitive response of potato to P. infestans (Wang et al, 2023). Besides deeper investigations in other host defence mechanisms, follow‐up studies on the identification of effectors or possible other small molecules that are responsible for PTI suppression by A. solani during infection of cultivated tomato plants could be of interest for further understanding of this host–pathogen interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Besides peptide effectors, Alternaria species can synthesize phytotoxic metabolites, such as AAL toxins and other host-specific or hostnonspecific toxins. Such toxins serve chemical inhibition of defence compounds produced by the host or the induction of cell death (Wang et al, 2023). There is limited information on the specific role of toxins of A. solani in pathogen infection.…”
Section: Discussionmentioning
confidence: 99%
“…There is limited information on the specific role of toxins of A. solani in pathogen infection. However, a recent study showed the effect of alternaric acid, a toxin of A. solani, on the hypersensitive response of potato to P. infestans (Wang et al, 2023). Besides deeper investigations in other host defence mechanisms, follow-up studies on the identification of effectors or possible other small molecules that are responsible for PTI suppression by A. solani during infection of cultivated tomato plants could be of interest for further understanding of this host-pathogen interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Pathogenic effectors are small, secreted proteins produced by pathogenic microbes that manipulate host cell structures and functions to facilitate infection and trigger defence responses. of host senescence genes (Wang, Xiao, et al, 2022;Wang et al, 2023).…”
Section: Protein Aceous Effec Tor Smentioning
confidence: 99%